PENERAPAN QUANTUM TEACHING UNTUK MENINGKATKAN KECER DASAN EMOSIONAL DAN PRESTASI BELAJAR MATEMATIKA - Lutfi Nur Hidayah; Tien Rukijah; Ahmad Ahmad (AlphaMath : Journal of Mathematics Education, 2018)
This class action research aims to improve the quality of emotional intelligence and mathematics learning achievement of students in class VII-F of SMP Negeri 5 Purwokerto by applying Quantum teaching to mathematics learning. After applying Quantum teaching emotional intelligence and mathematics learning achievement of students increased. This research was conducted in three cycles. Data collection techniques through observation by observers and filling out questionnaires by students, and data analysis was done in the description with scoring techniques. Based on the results of the research that has been done it can be concluded the following matters: 1) There is an increase in students' emotional intelligence in the process of learning mathematics. This can be seen from the increase in the average observations and emotional intelligence questionnaire results of students from cycle I to cycle III. In cycle III, the average results of observation of emotional intelligence were 2.53 with the criteria of emotionally intelligent students and the average results of students' emotional intelligence questionnaire in cycle III was 2.87 with the criteria of emotionally intelligent students. 2) There is an increase in students' mathematics learning achievement in the material lines and angles. This can be seen from the increase in grade point average and mastery learning. The average value of the class before the application of Quantum teaching was 72.21 with a mastery of learning at 54.54% after the implementation of the Quantun teaching completeness of student learning rose to 74.194% with an average grade of 76.548. Thus the application of Quantum teaching in mathematics learning succeeded in increasing emotional intelligence and mathematics learning achievement of VII-F graders of SMP Negeri 5 Purwokerto